English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2x + y = 6
x² + y² = 20

2007-10-22 07:27:51 · 11 answers · asked by Leo 3 in Science & Mathematics Mathematics

11 answers

First, square both sides of the first equation.

(2x+y)^2=6^2
4x^2+4xy+y^2=36.

Then use the elimination method and subtract the second equation from the new first equation.

4x^2+4xy+y^2=36
-(x^2 +y^2) =-20
3x^2+4xy =16

Then factor out x.

x(3x+4y) =16

Since 3x+4y can be rewritten as 4(2x+y) - 5x, substitute 2x+y into 4(2x+y) - 5x.

x(4 times 6 -5x)=16.

Simplify the equation.

-5x^2+24x-16=0
(-5x+4)(x-4)=0
x=4/5 or x=4

Then plug-in the two values of x back into the original first equation.

2 times 4/5 +y=6
2 times 4 + y =6

Simplify the equations.

8/5+y=6 or 8+y=6
y=22/5 or y= -2
x=4/5 or x= 4

(x,y)= (4/5,22/5) or (x,y)= (4, -2)

2007-10-22 07:52:45 · answer #1 · answered by yoo 2 · 0 0

Its referred to as algebraic technique because of the fact which you could desire to make certain what the variables (or letters) values are. Trial and mistake can paintings, even though it heavily isn't plenty use to you for greater durable equations. first element to do is to objective to do away with 1 variable via subtracting or including the equations jointly. you could no longer try this subsequently because of the fact which you will finally end up with the two variables nonetheless. So make the two the numbers till now the x's or the y's an identical like this: call the equations (a million) 5x + 3y = -a million and (2) 3x + 4y =6 Take (a million) and multiply it via 4 so which you have (3) 20x +12y = -4. Take (2) and multiply it via 3 to get (4) 9x +12y = 18. Now your numbers till now the y's are an identical so as which you will get rid of that variable. Take equation (3) and subtract (4) which aspects 11x = -22 so x = -2. placed this lower back into the two of the unique equations to paintings out the cost of y. In (a million) which skill (-2)*5 + 3y = -a million; -10 +3y = -a million. So 3y = 9 and y = 3. finally verify those are the main suitable solutions via putting them into equation (2): (3*-2)+(4*3) = (-6) + 12 = 6

2016-12-18 14:33:12 · answer #2 · answered by Anonymous · 0 0

2x + y = 6
x² + y² = 20
rearrange the top equation
y=6-2x
subsitute into the other equation
x^2 + (6-2x)^2 = 20
x^2 + (6-2x) (6-2x) = 20
x^2 + 36 -24x +4x^2 =20
5x^2 -24x +36=20
5x^2 -24x +16=0
(5x - 4) (x - 4)
x = 4/5, 4
y=6-2x
y=6-2(4/5)
y=6-1 3/5 = 4 2/5
y=6-2x
y=6-2(4) = -2
this gives co-ordinates of
(4/5, 4 2/5)
(4,-2)

2007-10-22 21:42:14 · answer #3 · answered by Anonymous · 0 0

Use substitution.

y = 6 - 2x

x^2 + (6-2x)^2 =20

x^2 + 36-12x-12x+4x^2 = 20

5x^2 -24x -16 =0

Now get the roots. Sub the roots into the other equation for 'y' values.

2007-10-22 07:34:28 · answer #4 · answered by de4th 4 · 0 0

y = 6 - 2x

Substitute for y in equation 2

x² + (6 - 2x)² = 20

x² + 36 - 24x + 4x² = 20

5x² - 24x + 16 = 0

(5x - 4) (x - 4) = 0

x = 4/5 or x = 4

Plugging into equation 1

y = 22/5 or y = -2

So x = 4/5 and y = 22/5 or

x = 4 and y = -2

I hope this helps.

2007-10-22 07:41:26 · answer #5 · answered by SUMMERWE 3 · 0 1

y = 6 - 2x
x² + (6 - 2x)² = 20
x² + 36 - 24x + 4x² = 20
5x² - 24x + 16 = 0
(5x - 4)(x - 4) = 0
x = 4/5 , x = 4

8/5 + y = 6
y = 22/5

8 + y = 6
y = - 2

Solution is ( 4/5 , 22/5 ) ; ( 4 , - 2 )

2007-10-28 07:51:59 · answer #6 · answered by Como 7 · 1 0

2x +y =6, so
y = 6 - 2x
xx + (6 - 2x)(6-2x) = 20
xx + 36 - 12x - 12x + 4xx = 20
5xx -24x +36 = 20
5xx - 24x + 16 = 0
(5x - 4)(x - 4) = 0

x = 4/5 & 4
y= 6 - 2x, so
y = 6 -2(4/5) = 4 2/5 and
y = 6-2(4) = -2

so, x= 4/5 and 4
y=4 2/5 and -2

2007-10-22 07:32:25 · answer #7 · answered by Anonymous · 0 0

y = 6 - 2x
x^2 + (6 - 2x)^2 = 20
x^2 + 36 - 24x + 4x^2 = 20
5x^2 - 24x + 16 = 0
(5x - 4)(x - 4) = 0
x = 4/5, 4

y = 6 - 2*(4/5)
y = 22/5

y = 6 - 2*(4)
y = -2

(x, y) = (4/5, 22/5) and (4, -2)

2007-10-22 07:33:45 · answer #8 · answered by mathguru 3 · 0 0

2 x + y = 6 =
x + y = square root of 20

2x+y=6 -
x+y=square root of 20

= x = 1.34

so y = 3.32

these are only approximates because of square rooting 20 leaves a long messy number...

Hopes this helps (but i'm not sure if it's 100% right...)

2007-10-22 07:39:50 · answer #9 · answered by jellyfish.of.jazz 2 · 0 0

I think: x=square root of + or - '-16/5'

Then sub this into the first equation to get y.

2007-10-22 07:35:34 · answer #10 · answered by Mark R 3 · 0 0

fedest.com, questions and answers